Dimensão curricular do novo ensino médio: o olhar dos docentes de uma escola do município de Cachoeiro de Itapemirim-ES - Vicentino, Adriana Brunharo (2023)
The aim of the research is to analyze teachers’ understanding of the of the new Secondary School curriculum in a state school in the municipality of Cachoeiro de Itapemirim, ES. To achieve this, a qualitative research approach was conducted, applying a Focus Group with a sample of twenty-six (26) teachers from the specified school, with no involvement of managers. Among them, seven (07) are from the Humanities and Applied Social Sciences area, eleven (11) from the Languages and their Technologies area, and eight (08) from the Natural Sciences and their Technologies, Mathematics and their Technologies area. In the research, the teachers presented their assessments and perspectives regarding the new Secondary School curriculum. The Focus Group was divided by areas of knowledge, enabling focused viewpoints for particular disciplines. The analyses undertaken were based on the Historical-Critical Pedagogy developed by Dermeval Saviani, whose primary objective is for the school to teach scientific content in order to cultivate a critical-reflexive citizen. The author emphasizes that the school has lost this focus over time, adding other themes to the school curriculum to the disadvantage of scientific knowledge, as evidenced in the research. Saviani’s theory is philosophically grounded in historical-dialectical materialism. Scientific knowledge is crucial for the dominated social class to have the same access to content as the bourgeois class, overcoming social inequalities and promoting an egalitarian society. During the Focus Group, it became evident that teachers faced difficulties in covering the content within a shortened timeframe, considering the reduction of class hours for some subjects, to the detriment of others that were added to the curriculum, creating obstacles for the teaching process. The restrictions faced by teachers reflect an education system aimed at maintaining a class-based society, facilitating the formation of workers for the job market. Consequently, students are encouraged to start working as soon as they finish Secondary School.